2009
DOI: 10.1016/j.jmb.2009.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Glycan Topology for Avian and Human Sialopentasaccharide Receptor Analogues upon Binding Different Hemagglutinins: A Molecular Dynamics Perspective

Abstract: Hemagglutinin (HA) binds to sialylated glycans exposed on the host cell surface in the initial stage of avian influenza virus infection. It has been previously hypothesized that glycan topology plays a critical role in the human adaptation of avian flu viruses, such as the potentially pandemic H5N1. Comparative molecular dynamics (MD) studies are complementary to experimental techniques including glycan microarray to understand better the mechanism of species specificity switch. The examined systems comprise e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
111
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(126 citation statements)
references
References 103 publications
14
111
1
Order By: Relevance
“…MD simulations provide detailed information on the molecular structures and unbinding pathways that govern the interaction forces. In free simulations we observed that each receptor takes a slightly different conformation, although hydrogen bonds between four HA residues (Tyr98, Gly135, Ser136, and Asn137) and the receptor were always present, which is consistent with previous simulations (21,22). These four amino acids belong to the base and loop 130 of the HA receptor-binding pocket and are highly important for binding to the receptor (1).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…MD simulations provide detailed information on the molecular structures and unbinding pathways that govern the interaction forces. In free simulations we observed that each receptor takes a slightly different conformation, although hydrogen bonds between four HA residues (Tyr98, Gly135, Ser136, and Asn137) and the receptor were always present, which is consistent with previous simulations (21,22). These four amino acids belong to the base and loop 130 of the HA receptor-binding pocket and are highly important for binding to the receptor (1).…”
Section: Discussionsupporting
confidence: 88%
“…These differences cannot be observed with experimental force spectroscopy, where single force peaks were detected during unbinding. It was shown previously that unbound LSTc in solution adopts multiple conformations, which are strongly reduced upon binding to HA (22). This intrinsic structural variability of the receptor is also present in our unbinding simulations.…”
Section: Discussionsupporting
confidence: 73%
“…Computational modeling simulations predict RDB-receptor complexes in which the guanidinium group of R189 contacts human SA-receptor analogs through hydrogen bonds with the axial hydroxyls of the carbohydrate moiety in the fifth position. In contrast, Q189 is not found to interact with LSTc, and to our knowledge this position has not been observed experimentally (31,32,34) or through extensive molecular dynamic simulations with other HA subtypes (49) to make significant contacts with human receptors. In the predicted complexes, the Q189R side chain is remote from receptor-binding interactions that have been proposed to be important for binding receptors with α2-3 linkages.…”
Section: Discussioncontrasting
confidence: 53%
“…Human H3N2 viruses isolated in cell culture were reported to bind with a high affinity to ␣2-6-linked sialosides, while viruses isolated in eggs often had increased specificity for ␣2-3-linked sialosides (19,20,28). The functional classification of avian and mammalian influenza virus receptors is further complicated since in vitro and tissue-binding assays have led to new working hypotheses involving glycan chain length, topology, and the composition of the inner fragments of the carbohydrate chain as additional receptor specificity determinants (9,17,65,66,82). However, the significance of these in vitro properties remains unknown, since the structures of the natural sialosides on host cells that are used for infectious virus entry are undefined.…”
mentioning
confidence: 99%